Pericarp anatomy in relation to fruit cracking in lemon (Citrus limon) - Josan, J S; Sandhu, A S; Kaur, Jasbir (The Indian Journal of Agricultural Sciences, 2012)
An anatomical study of the pericarp of the normal, cracked and sun-scalded fmits of lemon [Citrus limon (L.) Burm. f.] was carried out during 1989 and 1990. Thickness of peel and epidermis-cum-cuticle of normal fruit (2.17 mm; 10.99Âµm) was more than that ofthecl’acked (1.98mm; 10.29Âµm) and sun-scalded (1.38 mm; 8.40Âµm) fruits. The normal and cracked fruits did not differ in compactness of their parenchyma cells, whereas sun-scalded fruits showed more flattening of these cells. The number of vascular bundles/mm2 in the peel of normal cracked and sun-scalded fruits were equal. However, they were deeper in the peel of normal fruits than in those of the cracked and sun-scalded fruits. The cracking started from the inner side of the peel and proceeded upward along the vascular bundles. Thus thickness of peel and epidermis-cum-cuticle and the number depth and arrangement of vascular bundles were found to play a major role in fruit cracking of lemon.